Investigating the Use of Element Analysis for Differentiation between the Geographic Origins of Western Cape Wines - Minnaar, P.P.; Rohwer, E.R.; Booyse, M. (South African Journal of Enology and Viticulture, 2017)
The aim of this study was to differentiate between the geographic origins of wines produced in the Western Cape on the basis of their element composition. A total of 96 market-ready red and white wines (Pinotage, Shiraz, Merlot, Cabernet Sauvignon, Sauvignon blanc, Chardonnay and Chenin blanc) were analysed by means of inductively coupled plasma atomic emission spectrometry (ICP-AES). The discriminant methods: stepwise discriminant analysis, canonical discriminant analysis and linear discriminant analysis were applied to the data sets. A classification accuracy of 38% for Pinotage, 55% for Shiraz, 68% for Merlot, 75% for Cabernet Sauvignon, 93% for Sauvignon blanc, 68% for Chardonnay and 100% for Chenin blanc was achieved. Subject to the conditions of this study, it was concluded that differentiation between wines according to geographical origin was possible using the elemental composition.